1997
DOI: 10.1007/bf00004669
|View full text |Cite
|
Sign up to set email alerts
|

The role of cortisol in amino acid mobilization and metabolism following exhaustive exercise in rainbow trout (Oncorhynchus mykiss Walbaum)

Abstract: The role of cortisol in the mobilization and metabolism of amino acids following exhaustive exercise in rainbow trout (Oncorhynchus mykiss) was investigated. Plasma cortisol levels were elevated for 4h following exercise and 6, of a total of 22 amino acids, showed significant responses. In white muscle, alanine and glutamine were elevated immediately after exercise through to 4h, whereas glutamate, and the branchedchain amino acids (BCAA), isoleucine, leucine and valine, all decreased over this time. In plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…After 6 hours of confinement the decrease was followed by an elevation in plasma total amino acid concentration that in LR fish reached significantly higher values than HR, which only returned to pre-stress basal levels. A number of authors have reported an increase in plasma amino acids after exhaustive exercise, handling, or confinement (Morales et al, 1990;Braley and Anderson, 1992;Milligan, 1997;Vijayan et al, 1997). It has been shown that elevated cortisol levels can provoke a net catabolism of peripheral proteins (synthesis is also inhibited) and an elevation of plasma free amino acid levels would be followed by a gluconeogenic removal (van der Boon et al, 1991;Vijayan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 6 hours of confinement the decrease was followed by an elevation in plasma total amino acid concentration that in LR fish reached significantly higher values than HR, which only returned to pre-stress basal levels. A number of authors have reported an increase in plasma amino acids after exhaustive exercise, handling, or confinement (Morales et al, 1990;Braley and Anderson, 1992;Milligan, 1997;Vijayan et al, 1997). It has been shown that elevated cortisol levels can provoke a net catabolism of peripheral proteins (synthesis is also inhibited) and an elevation of plasma free amino acid levels would be followed by a gluconeogenic removal (van der Boon et al, 1991;Vijayan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated cortisol levels can provoke a net catabolism of peripheral proteins (synthesis is also inhibited) and an elevation of plasma free amino acid levels would be followed by a gluconeogenic removal (van der Boon et al, 1991;Vijayan et al, 1997). High plasma amino acid levels lead to induction of liver aminotransferases and consequently the participation of these metabolites in hepatic gluconeogenesis (Morales et al, 1990;van der Boon et al, 1991;Milligan, 1997). Several studies have provided evidence that alanine constitutes a good hepatic gluconeogenic precursor in fish (Medale et al, 1987;Braley and Anderson, 1992;Vijayan et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mommsen (51) suggested that the spawninginduced salmon muscle degenerative mechanisms involve glucocorticoids. Fish spawning (11,38), and intense exercise (49) increase activity of the pituitary-interrenal axis, increasing cortisol availability. This observation suggests that altered gene expression of glycolytic pathway enzymes may be subsequent to insulin resistance caused by prolonged partial anorexia or as a downstream effect of elevated levels of adrenal glucocorticoids.…”
Section: Genes Involved In Glucose Metabolismmentioning
confidence: 99%
“…after exercise and lasted for several hours15. Both of these hormones are closely related to the metabolic regulation of carbohydrates, proteins, amino acids and lipids after exercise, and the mechanism of the regulation is related to the hormone receptors [15][16][17].…”
Section: Resultsmentioning
confidence: 99%